Beneficial effects of proanthocyanidins on skin aging: a review - Ye, Hua; Sun, Jiaqiang; He, Linlin; Ai, Chenyue; Jin, Wengang; Abd El-Aty, A. M. (Frontiers in Nutrition, 2025)
Skin aging is a gradual physiological process influenced by both intrinsic and environmental factors and is characterized by the appearance of wrinkles, pigmentation, reduced elasticity, dryness, and vascular changes. In recent years, interest in the use of natural bioactive compounds to mitigate skin aging has increased, reflecting the global shift toward safer, sustainable, and health-conscious skincare solutions. Proanthocyanidins (PCs), a class of polyphenolic compounds derived from plant sources, exhibit strong antioxidant, anti-inflammatory, and antipigmentation properties. These compounds have considerable potential for enhancing the structure and function of aged skin by reducing oxidative stress, promoting collagen and elastin synthesis, alleviating the skin inflammatory response, and inhibiting pigmentation. Despite their promising therapeutic value, the efficacy of PCs can be compromised by their environmental instability and low bioavailability. Advances in encapsulation techniques and combination formulations have shown promise in enhancing the stability and delivery efficiency of PCs, thereby improving their performance in antiaging applications. In conclusion, PCs offer a scientifically grounded and sustainable approach for addressing skin aging. Their integration into dermatological products represents an innovative and eco-conscious strategy for developing next-generation skincare solutions with broad health and consumer benefits.